Rethinking the property rights of spouses on civil marriage breakdown in Nigeria : inspiration from other countries - Van Schalkwyk, L.N. (Llewelyn Neil), 1952- (University of Pretoria, 2018)
Thesis (LLD)--University of Pretoria, 2017.